Knowledge as Resistance : The Feminist International Network of Resistance to Reproductive and Genetic Engineering - de Saille, Stevienna (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book presents a historicised account of the Feminist International Network of Resistance to Reproductive and Genetic Engineering (FINRRAGE), a coordinated effort during the 1980s and 1990s by an international group of women to create and disseminate feminist knowledge about the then-new field of reproductive technologies. Bringing insights from science and technology studies together with social movements and feminist theory, it seeks to examine larger questions about knowledge and expertise in activist engagements with rapidly-developing technologies, as well as explore an important and neglected episode of feminist history. Its findings will be relevant to scholars in science studies, gender and women's studies and social movements, as well as to anyone with an interest in reproductive technologies and the history of feminist activism.- Resumé vydavatel